Humor nas propagandas televisivas: um olhar qualitativo sobre as percepções dos consumidores - Silva, Hélcia Daniel da (Universidade do Vale do Rio dos Sinos, 2010)
Advertising plays an important role for society, economy and business market. Its value in marketing is crucial, as the leading tool for public exposure, can change behavior and attitudes, charming and persuading them with varied and appeals that make a difference in the context propaganda. The humor is irreverent and considered an appeal of success when properly used in the materials. It is a resource that can facilitate the interests of consumers by the message. The objective of this study was to deepen the understanding of consumers perceptions of the humor present in television advertisements. Stands out, however, that there are few studies that refer the appeal humor in Brazil, specifically in television advertisements. To that end, this paper contributes to the topic, presenting bibliographical studies author seminal and a qualitative study describing the method of theoretical sampling, specifically as in-depth interview, covering twelve women, spoken as housewives and professional market, which say they enjoy watching television, with various biographical characteristics (age, marital status, occupation) and consequently with very different behavioral Characteristics. In methodological steps, participants were interviewed separately (one by one), totaling nine questions, but noting, where necessary the creation of sub-questions in order to instigate and make them talk and express feelings, emotions and values. The method of this interview exposes these conditions, remembering that their intention is to raise all these behavioral data to meet the study. The interviewer said to the researcher (Strauss, 2008) tendency not the answers but does the interviewees respond in detail to involve them trying to understand and thus deepen in its forms of verbal or nonverbal communication the matter proposed. After this step, make up the analysis by comparing and evaluating responses in a systemic view and a focus depth look that they have in relation to humor in advertising. Given this proposal, the study finds that there is a positive attitude, a look at the remarkable acceptance of humor in advertisements that conditions influencing and ends in the question and remembrance in calling the attention of the viewer, although the mood attribute should be attached to other elements Key which help promote and persuasion, such as contextual creativity, the need for vision products in the consumer price, the names, characters, among others. The fact accept and see humor as a strong call said as differential can establish a direct relationship with the intention of buying, but in this condition, further studies are needed and different methods to admit this hypothesis accurately. With the study, one can see that the individual sees the humorous advertisement, when well done with good eyes, according to the interviewees, the shopping is in remembrance of the individual, associate product advertising, and as a consequence serves as an aid in the purchase. As for the academic implications and suggestions for future studies continue to be exposed at the end of the dissertation.
Keywords: Propaganda; Atributo humor; Percepção; Comportamento; Intenção de compra; Advertising; Attribute mood; Perception; Behavior; Purchase intent; ACCNPQ::Ciências Sociais Aplicadas::Administração